The Effect of Rapid Cooling on the Corrosion Resistance of As-Cast Aluminium Alloy 5052 - Szklarz, Zbigniew; Krawiec, Halina; Rogal, Łukasz (Journal of Casting & Materials Engineering, 2017)
The effect of rapid cooling by the vacuum suction casting method (VSC) on the microstructure and electrochemical response of the as-cast 5052 aluminium alloy is presented. The VSC method allowed us to obtain massive samples witha very high cooling rate (102 – 103) oC/s. The microstructure of the quick-cooled sample (QC) has been significantly changed. Finer grains and more-homogeneous intermetallic phase distribution has been observed. Corrosion potential (OCP) and polarization measurements (LSV) revealed a higher activity of the QC alloy than ingot (IN), which leads to a denser and thicker corrosion-product formation on the surface. Electrochemical Impedance Spectroscopy (EIS) indicates higher resistance values, which suggests a greater thickness of the corrosion products.